Neural Integration of Risk and Effort Costs by the Frontal Pole: Only upon Request - Burke, Christopher J. (J Neurosci, 2013)
Rewards in real life are rarely received without incurring costs and successful reward harvesting often involves weighing and minimizing different types of costs. In the natural environment, such costs often include the physical effort required to obtain rewards and potential risks attached to them. Costs may also include potential risks. In this study, we applied fMRI to explore the neural coding of physical effort costs as opposed to costs associated with risky rewards. Using an incentive-compatible valuation mechanism, we separately measured the subjective costs associated with effortful and risky options. As expected, subjective costs of options increased with both increasing effort and increasing risk. Despite the similar nature of behavioral discounting of effort and risk, distinct regions of the brain coded these two cost types separately, with anterior insula primarily processing risk costs and midcingulate and supplementary motor area (SMA) processing effort costs. To investigate integration of the two cost types, we also presented participants with options that combined effortful and risky elements. We found that the frontal pole integrates effort and risk costs through functional coupling with the SMA and insula. The degree to which the latter two regions influenced frontal pole activity correlated with participant-specific behavioral sensitivity to effort and risk costs. These data support the notion that, although physical effort costs may appear to be behaviorally similar to other types of costs, such as risk, they are treated separately at the neural level and are integrated only if there is a need to do so.